Pengaruh Customer Review, Bundling Promotion, dan Brand Image Terhadap Keputusan Pembelian Produk Skincare The Originote pada Platform Tiktokshop di Kota Batam - Junaidi, Ayu Ani Angraini; Mulyadi Luthfi, Andi; Yantri, One (Universitas Batam, 2025)
This research aims to determine and analyze the influence of Customer Review, Bundling Promotion, and Brand Image on Purchase Decisions of The Originote skincare products through the TikTokShop platform in Batam City. The method used in this research is quantitative. The population consists of people in Batam City; however, since not all use The Originote products, the population size is considered unknown. The sample consisted of 96 respondents selected using purposive sampling. Data were collected using a questionnaire that was tested for validity and reliability. Data analysis included classical assumption tests, multiple linear regression, t-test, F- test, and coefficient of determination, using SPSS software version 27. The results showed that bundling promotion and brand image partially had a positive and significant effect on purchase decisions, while customer review had a positive but not significant effect. Simultaneously, all three variables had a positive and significant influence on the purchase decision of The Originote products through the TikTokShop platform in Batam City.